2022
DOI: 10.1038/s41598-022-07992-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the decoding accuracy of EEG signals by the introduction of anchored-STFT and adversarial data augmentation method

Abstract: Brain-computer interfaces (BCIs) enable communication between humans and machines by translating brain activity into control commands. Electroencephalography (EEG) signals are one of the most used brain signals in non-invasive BCI applications but are often contaminated with noise. Therefore, it is possible that meaningful patterns for classifying EEG signals are deeply hidden. State-of-the-art deep-learning algorithms are successful in learning hidden, meaningful patterns. However, the quality and the quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Henceforth, the development of a reliable and robust muscle-to-machine interfaces decoder remains one of the primary goals of the brain-machine interface (BMI) community. Real life applications, such as control of prosthesis, rehabilitation-aiding exoskeletons, and BMI for gaming are active research areas [1]. Recently published studies on movement classification based on sEMG showed promising results with high accuracy and real-time processing capabilities [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Henceforth, the development of a reliable and robust muscle-to-machine interfaces decoder remains one of the primary goals of the brain-machine interface (BMI) community. Real life applications, such as control of prosthesis, rehabilitation-aiding exoskeletons, and BMI for gaming are active research areas [1]. Recently published studies on movement classification based on sEMG showed promising results with high accuracy and real-time processing capabilities [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…But the proposed model has outperformed the baseline methods by generating a TFR of the MI data from 2 channels, thereby having lesser complexity than the model used in [38]. The method proposed in [28] has classified the left and right hand MI tasks with an accuracy of 81.2% by using the MI EEG data from 3 channels, an anchored STFT for feature extraction and a skip-net CNN model with data augmentation techniques. The method proposed in this study has attained a slightly higher accuracy as compared to [28] by using the data from lesser number of channels and a CNN model with a simple architecture.…”
Section: Comparison Of Results For Different N Valuesmentioning
confidence: 99%
“…The method proposed in [28] has classified the left and right hand MI tasks with an accuracy of 81.2% by using the MI EEG data from 3 channels, an anchored STFT for feature extraction and a skip-net CNN model with data augmentation techniques. The method proposed in this study has attained a slightly higher accuracy as compared to [28] by using the data from lesser number of channels and a CNN model with a simple architecture. Similarly, it gives a higher accuracy than [39] which uses Sliding Window (SW) to extract nine timeframes of length 1 sec from the MI data of multiple channels and uses CSP and LDA for feature extraction and classification of data in each frame respectively.…”
Section: Comparison Of Results For Different N Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques involve a variety of methodologies aimed at increasing the adaptability and accuracy of MI-EEG classification models. Broadly categorized, these techniques can be divided into two principal categories: those that operate on the manipulation of raw EEG waveforms and those that leverage domain transformation techniques [18][19][20], such as short-time Fourier transform (STFT) [21], to derive augmented data in the alternative domains (e.g. frequency domain, time-frequency domain, spatial domain).…”
Section: Related Workmentioning
confidence: 99%